2009
DOI: 10.1055/s-0028-1112206
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Barakol under Hydrolytic Stress Conditions and its Major Degradation Product

Abstract: The aim of the present study was to investigate the stability of barakol, an anxiolytic constituent extracted from leaves of Senna siamea (Lam.) Irwin & Barneby (syn. Cassia siamea Lam.), under the International Conference on Harmonisation suggested conditions using HPLC with photodiode array detection. Extensive degradation of barakol was found to occur under alkaline conditions through base-catalyzed hydrolysis. Mild degradation of barakol was observed under thermal and oxidative stress while it was stable u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…All identification data were similar to standard barakol reported in previous publications (Padumanonda et al 2007;Chantong et al 2009). The identification results indicated that the extracted chemical constituent from fresh young leaves of S. siamea was barakol.…”
Section: Identification Of Extracted Barakolsupporting
confidence: 69%
See 1 more Smart Citation
“…All identification data were similar to standard barakol reported in previous publications (Padumanonda et al 2007;Chantong et al 2009). The identification results indicated that the extracted chemical constituent from fresh young leaves of S. siamea was barakol.…”
Section: Identification Of Extracted Barakolsupporting
confidence: 69%
“…Barakol exhibits hypnotic effect in both animals and human volunteers and has been used as a medicinal agent by insomniacs. But, the Food and Drug Administration of Thailand removed the products containing S. siamea leaves from the market due to their hepatotoxicity (Chantong et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the level of hepatic cytochrome P450 (CYP) in barakoltreated mice was observed (Devakul Na Ayutthaya et al, 2005) and CYP was found to be a key enzyme in controlling differentiation of P19 cells (Sonneveld et al, 1999). Barakol, which contains a phenolic moiety, might be metabolized by CYP isozymes into anhydrobarakol, a semi-quinone (Thongsaard et al, 2001) or cassiachromone, a chromone (Chantong et al, 2009) (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
“…1) as previously described (Chantong et al, 2009). Briefly, the leaves were boiled with 5% sulfuric acid for 15 min, filtered and alkalinized with sodium bicarbonate (10% w/v).…”
Section: Isolation Of Barakolmentioning
confidence: 99%
“…As principais correlações observadas no mapa de contorno HMBC (Figuras 155−157; Tabela 29) entre δH 2,28 (H-14) com δC 164,5 (C-2) ( 2 JH→C) e δC 110,3 (C-3) ( 3 JH→C); entre δH 5,95 (H-3) com δC 164,5 (C-2) ( 2 JH→C), δC 113,9 (C-10) ( 3 JH→C) e δC 19,4 (C-14) ( 3 JH→C); permitiram confirmar o padrão de substituição do anel γ-pirona. Assim como as correlações entre δH 6,58 (H-6) com δC 161,1 (C-7) ( 2 JH→C), δC 101,3 (C-8) ( 3 JH→C), δC 113,9 (C-10) ( 3 JH→C) e δC 48,9 (C-11) ( 3 JH→C); entre δH 6,70 (H-8) com δ C 177,7 (C-4) ( 4 J H→C ), δ C 118,1 (C-6) ( 3 J H→C ), δ C 161,1 (C-7) ( 2 J H→C ), δ C 159,0 (C-9) ( 2 JH→C) e δC 113,9 (C-10) ( 3 JH→C); entre δH 4,11 (H-11) com δC 138,3 (C-5) ( 2 JH→C), δC 118,1 (C-6) ( 3 JH→C), δC 113,9 (C-10) ( 3 JH→C) e δC 204,5 (C-12) ( 2 JH→C); entre δH 2,18 (H-13) com δC 138,3 (C-5) ( 4 JH→C), δC 48,9 (C-11) ( 3 JH→C), δC 204,5 (C-12) ( 2 JH→C), que permitiram confirmar o padrão de substituição do anel aromático (Figura 148; Tabela 29).Os dados de RMN (Tabelas 28 e 29; Figuras 151−157), aliados aos dados de EM e UV-Vis foram similares aos publicados na literatura(CHANTONG et al, 2009;SINGH, 1982) e são consistentes com a estrutura da 5-acetonil-7-hidroxi-2-metilcromona (VII), também conhecida como cassiacromona.Tabela 28 -Dados de RMN de 1 H e 13 C (400/100 MHz, DMSO-d6) do composto VII em comparação com dados da literatura. Deslocamentos químicos estabelecidos em relação ao padrão interno TMS (δTMS = 0,0 ppm).…”
unclassified